A Reusable Mesoporous Nickel Nanocomposite Catalyst for the Selective Hydrogenation of Nitroarenes in the Presence of Sensitive Functional Groups. Issue 15 (8th July 2016) - Hahn, Gabriela; Ewert, Julia‐Katharina; Denner, Christine; Tilgner, Dominic; Kempe, Rhett
Abstract: The synthesis of aromatic amines from nitroarenes through hydrogenation is an industrially and academically important reaction. In addition, the employment of base metal catalysts in reactions that are preferentially mediated by rare noble metals is a desirable aim in catalysis and an attractive element‐conservation strategy. Especially appealing is the observation of novel selectivity patterns with such inexpensive metal catalysts. Herein, we report a novel mesostructured Ni nanocomposite catalyst. It is the first example of a reusable Ni catalyst that is able to hydrogenate nitroarenes selectively to anilines in the presence of highly sensitive functional groups such as C=C bonds and nitrile, aldehyde, and iodo substituents. Abstract : Why so sensitive? A novel mesostructured Ni nanocomposite catalyst that is easy to synthesize and scale up is introduced. It is a reusable catalyst for the selective hydrogenation of nitroarenes to anilines. Highly hydrogenation‐sensitive groups such as olefins and aldehydes are tolerated.